1996
DOI: 10.1161/01.cir.94.9.2216
|View full text |Cite
|
Sign up to set email alerts
|

Anorexic Agents Aminorex, Fenfluramine, and Dexfenfluramine Inhibit Potassium Current in Rat Pulmonary Vascular Smooth Muscle and Cause Pulmonary Vasoconstriction

Abstract: These observations indicate that anorexic agents, like hypoxia, can inhibit potassium current, cause membrane depolarization, and stimulate pulmonary vasoconstriction. They suggest one mechanism that could be responsible for initiating pulmonary hypertension in susceptible individuals. It is possible that susceptibility is the result of the reduced production of an endogenous vasodilator, such as NO, but this remains speculative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
1
5

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(117 citation statements)
references
References 27 publications
3
108
1
5
Order By: Relevance
“…Briefly, under pathological conditions, pulmonary endothelial cells produce high levels of serotonin that acts in a paracrine fashion on adjacent PASMCs to promote cell proliferation and contraction [26][27][28]. Results showing that exposure of human normotensive PASMCs to aminorex, fenfluramine or dexfenfluramide (appetite suppressant drugs that interact with the metabolism of serotonin) reduces the expression of K V 1.5 and inhibits K + current support the notion that serotonin signalling causes PAH, at least in part, through its effect on K V channel gene regulation [29,30]. COGOLLUDO et al [31] reported that serotonin treatment of PASMCs or Ltk − cells expressing cloned ] cyt : cytoplasmic free calcium concentration; Em: membrane potential; PI3K: phosphoinositide 3-kinase; PIP 2 : phosphatidylinositol-4,5-biphosphate; IP 3 : inositol-1,4,5-triphosphate; DAG: diacylglycerol; PLC: phospholipase C; PKC: protein kinase C; SrcTK: Src family tyrosine kinase; MLCK: myosin light-chain kinase; ROS: reactive oxygen species; HIF-1α: hypoxia-inducible factor-1α; PDK1: pyruvate dehydrogenase kinase, isozyme 1; HXK2: hexokinase 2; NFAT: nuclear factor of activated T-cells; STAT3: signal transducer and activator of transcription 3; SMAD: Mothers against decapentaplegic homologue; MAPK: mitogen-activated protein kinases; ψm: mitochondrial membrane potential; ET-R: endothelin receptor; BMP: bone morphogenetic protein; BMPRII: BMP receptor type II; TP: thromboxane receptor; 5-HTR: 5-hydroxytryptamine receptor; TNF-α: tumour necrosis factor-α; IL-6: interleukin-6; PDGF: platelet-derived growth factor; FGF: fibroblast growth factor; TNFR: TNF receptor; IL-6R: IL-6 receptor; RTK: receptor tyrosine kinases.…”
Section: Potassium Channels In Regulation Of Cell Proliferation and Cmentioning
confidence: 74%
“…Briefly, under pathological conditions, pulmonary endothelial cells produce high levels of serotonin that acts in a paracrine fashion on adjacent PASMCs to promote cell proliferation and contraction [26][27][28]. Results showing that exposure of human normotensive PASMCs to aminorex, fenfluramine or dexfenfluramide (appetite suppressant drugs that interact with the metabolism of serotonin) reduces the expression of K V 1.5 and inhibits K + current support the notion that serotonin signalling causes PAH, at least in part, through its effect on K V channel gene regulation [29,30]. COGOLLUDO et al [31] reported that serotonin treatment of PASMCs or Ltk − cells expressing cloned ] cyt : cytoplasmic free calcium concentration; Em: membrane potential; PI3K: phosphoinositide 3-kinase; PIP 2 : phosphatidylinositol-4,5-biphosphate; IP 3 : inositol-1,4,5-triphosphate; DAG: diacylglycerol; PLC: phospholipase C; PKC: protein kinase C; SrcTK: Src family tyrosine kinase; MLCK: myosin light-chain kinase; ROS: reactive oxygen species; HIF-1α: hypoxia-inducible factor-1α; PDK1: pyruvate dehydrogenase kinase, isozyme 1; HXK2: hexokinase 2; NFAT: nuclear factor of activated T-cells; STAT3: signal transducer and activator of transcription 3; SMAD: Mothers against decapentaplegic homologue; MAPK: mitogen-activated protein kinases; ψm: mitochondrial membrane potential; ET-R: endothelin receptor; BMP: bone morphogenetic protein; BMPRII: BMP receptor type II; TP: thromboxane receptor; 5-HTR: 5-hydroxytryptamine receptor; TNF-α: tumour necrosis factor-α; IL-6: interleukin-6; PDGF: platelet-derived growth factor; FGF: fibroblast growth factor; TNFR: TNF receptor; IL-6R: IL-6 receptor; RTK: receptor tyrosine kinases.…”
Section: Potassium Channels In Regulation Of Cell Proliferation and Cmentioning
confidence: 74%
“…Thickening of the heart valves, most often aortic and mitral, was seen along with thickening and shortening of the chordae tendineae, with subsequent valvular regurgitation [58,59] after chronic use. In addition, primary pulmonary hypertension has also been linked to chronic fenfluramine use; the absolute risk was 30 times greater in people using anorectic agents for greater than 3 months [60].While the pathophysiology is not clear, it is thought that serotonin acts as a vascocontrictor [61]. Flenfluramine and the combination Fen-Phen® was officially withdrawn in 1997 following Connolly et al's publication of valvular abnormalities in relation to its use.…”
Section: Fenfluramine/serotonergic Agentsmentioning
confidence: 99%
“…Anoreksijen ilaçlar serotonin geri alınımını (re-uptake) inhibe ederler ve serotonin salınımına neden olurlar, bunun yanında K kanallarını da bloke ederler. Sonuçta bu ilaçla-rın kullanımı ile trombositler sürekli depolarize durumdayken, pulmoner arter düz kas hücreleri ise sürekli serotoninemik bir vasküler tonusa maruz kalırlar (35).…”
Section: Ekstrasellüler Matriks Döngüsü Ve Enzimatik Etkileşimlerunclassified
“…Ayrıca bazı hayvan modellerinde Kv1.5'un yanında KV2.1'in de azalmış olduğu gösterilmiştir (38). İştah kesici ilaçlardan aminoreks ve deksfenfluraminin de Kv1.5 ve Kv2.1 inhibisyonu yaptığı bilinmektedir (35).…”
Section: Ekstrasellüler Matriks Döngüsü Ve Enzimatik Etkileşimlerunclassified